2015
DOI: 10.1002/mus.24629
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal 2-point dixon muscle magnetic resonance imaging in becker muscular dystrophy

Abstract: As in other myopathies, 2PD can quantify fatty muscle degeneration in BMD and can detect disease progression in a small sample size and at relatively short imaging intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
3
14
0
2
Order By: Relevance
“…In a natural history study of patients with LGMD2I, a significant increase in muscle fat fraction has been reported throughout a one-year follow-up whereas no changes were reported for any of the conventional longitudinal physical assessments [15]. Accordingly, in a small group of patients with Becker Muscular Dystrophy [18], the rate of fat fraction change was 3.7%/year whereas the clinical changes measured by the MFM were relatively mild, with a decrease of around 1%/year. In a recent one-year longitudinal study of patients with Duchenne muscular dystrophy (DMD), Bonati et al reported a significant increment of the mean fat fraction in all the patients and all studied thigh muscle groups [17], a significant decrease of mean MFM total score (2.9%/year) and a highly negative correlation between clinical scores (MFM total and D1 subscore) and thigh mean fat fraction values longitudinally (r = −0.71).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a natural history study of patients with LGMD2I, a significant increase in muscle fat fraction has been reported throughout a one-year follow-up whereas no changes were reported for any of the conventional longitudinal physical assessments [15]. Accordingly, in a small group of patients with Becker Muscular Dystrophy [18], the rate of fat fraction change was 3.7%/year whereas the clinical changes measured by the MFM were relatively mild, with a decrease of around 1%/year. In a recent one-year longitudinal study of patients with Duchenne muscular dystrophy (DMD), Bonati et al reported a significant increment of the mean fat fraction in all the patients and all studied thigh muscle groups [17], a significant decrease of mean MFM total score (2.9%/year) and a highly negative correlation between clinical scores (MFM total and D1 subscore) and thigh mean fat fraction values longitudinally (r = −0.71).…”
Section: Discussionmentioning
confidence: 98%
“…The corresponding quantitative MRI (qMRI) indices have not been approved yet by the European Medical Agencies as surrogate outcome measures in clinical trials [11]. In previous studies, qMRI has been used to describe the natural progression of neuromuscular disorders such as oculopharyngeal muscular dystrophy, Charcot-Marie-Tooth disease 1A, inclusion body myositis, LGMD2I and dystrophinopathies [13][14][15][16][17][18][19] and to characterize changes resulting from therapeutic trials [20]. Overall, it has been shown that muscle MRI can be more sensitive than clinical scores to detect disease progression during the follow-up of patients with muscular dystrophies [14,15] thereby highlighting the qMRI potential for the noninvasive assessment of disease progression and the characterization of treatment efficiency in neuromuscular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Lorsque le pourcentage de graisse atteint 50 %, ce signe a une valeur prédictive élevée de la perte de la marche dans l'année (Fischmann et al 2013). Sur une petite cohorte de 3 adultes atteints de la maladie de Becker, le taux annuel d'infiltration graisseuse a été évalué à 3.7 % dans la cuisse (Bonati et al 2015b). En combinant les pourcentages de graisse avec une segmentation manuelle des muscles, on a pu déterminer des indices de masse contractile chez les patients atteints de la maladie de Duchenne (Wokke et al 2014b).…”
Section: Les Altérations Dégénératives Chroniquesunclassified
“…В небольшой группе из 3 взрос-лых пациентов с ПМД Беккера скорость жировой инфильтрации на бедре составила 3,7 % в год [75]. У пациентов с ПМД Дюшенна в режиме ручной сег-ментации мышц и ППС сократительных тканей опре-деляется похожий процент жирового распределения [44].…”
Section: лекции и обзорыunclassified